2018
DOI: 10.11124/jbisrir-2017-003386
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Minimum Data Sets for documenting nutritional care for adults in primary healthcare: a scoping review

Abstract: The nutritional screening instruments have solely been validated in an over-55 population. Construct validity was the type of validation most frequently used in the validation process covering a total of 25 of the 29 tools. Two studies were identified in relation to the third review question. These two documents are both consensus statement documents developed by experts within the geriatric and nutritional care field. Overall, experts find it appropriate to: i) conduct a comprehensive geriatric assessment, ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…First, a systematic scoping review using The Joanna Briggs Institute's approach for the conduct of systematic scoping reviews was utilized to map the available evidence underpinning the development of an MDS. 51,52 Second, the data included from the scoping review were analysed using the content analysis approach [53][54][55] (see Figure 1).…”
Section: Designmentioning
confidence: 99%
“…First, a systematic scoping review using The Joanna Briggs Institute's approach for the conduct of systematic scoping reviews was utilized to map the available evidence underpinning the development of an MDS. 51,52 Second, the data included from the scoping review were analysed using the content analysis approach [53][54][55] (see Figure 1).…”
Section: Designmentioning
confidence: 99%
“… 13 Cooperation and communication among healthcare providers are important to ensure that patients receive proper and coordinated nutritional treatment and care. 14 Individualised care acknowledges the uniqueness of the individual, and may improve the quality of nutritional care in cases of complex nutritional problems. One randomised controlled trial (RCT) study indicated that individualised nutritional treatment improves energy intake and the activities of daily living (ADLs) of older patients who had an acute stroke with malnutrition risk, as compared with a standard care group.…”
Section: Introductionmentioning
confidence: 99%
“… 18–20 However, lack of continuity in care and poor communication have been identified as important risk factors for malnutrition. 14 21 22 …”
Section: Introductionmentioning
confidence: 99%
“…Nutritional issues or malnutrition neither occur nor are solved overnight. Communication and collaboration among different healthcare providers are of utmost importance to ensure that patients receive coherent and coordinated nutritional care and treatment 13…”
Section: Introductionmentioning
confidence: 99%
“…With shorter hospital stays, there will be an increased need for nutrition services after discharge to support improvements in nutritional status to prevent complications and re-admission 16–18. However, lack of communication and continuity in care has been identified in several studies as a major risk factor for malnutrition 13 19 20…”
Section: Introductionmentioning
confidence: 99%